How do crate materials impact the winter transport of broilers? - Myunghwan Yu; Elijah Ogola Oketch; Nuwan Chamara Chathuranga; Shan Randima Nawarathne; Venuste Maniraguha; Bernadette Gerpacio. Sta. Cruz; Eunsoo Seo; Jeseok Lee; Jung Min Heo (Animal Bioscience)
Objective Pre-slaughter transportation adversely impacts the welfare, meat yield, and quality of broilers, yet the effects of different crate types on broiler chickens during winter remain underexplored. The goal of this study was to investigate the effect of plastic and iron crates in transit on meat quality, carcass, and physiological traits of broiler chickens during winter. Methods A total of 175 (35-day-old) Ross 308 male broilers with an average body weight of about 1,708±33.3 g (mean±standard error of the mean) were picked after 4 hours of feed withdrawal before transport. The control group comprises birds in the farm (n = 15) without transportation at 173 cm2/kg density. The birds were transported into fixed iron (25 birds per crate) and plastic crates (15 birds per crate) with four replicates per crate type at the same 173 cm2/kg densities. The transportation distance was 20 km for 40 min at an average speed of 30–50 km/h early morning at 8:00 am under −1°C and 47% relative humidity. Results There was no difference (p>0.05) in carcass traits among the treatments. Concerning meat quality, broilers transported in both crate types exhibited lower (p<0.01) a* values compared to the control group. Additionally, the iron crate group demonstrated higher (p<0.05) b* values for the breast meat compared to the other groups. In terms of blood metabolites, the iron crate group had higher (p<0.05) cortisol, glucose, and lactate levels compared to the control group that did not transport. Conclusion Broilers transported in the iron crates increase stress levels in terms of higher cortisol, glucose, and lactate contents in the blood plasma compared to untransported broilers during the winter. Therefore, employing plastic crates, which induce significantly reduced cortisol and numerically lower glucose levels compared to iron crates, appears more favorable for animal welfare by mitigating stress.